2019
DOI: 10.1128/aac.01650-19
|View full text |Cite
|
Sign up to set email alerts
|

Renal Glycosuria as a Novel Early Sign of Colistin-Induced Kidney Damage in Mice

Abstract: The polymyxin colistin represents a last-resort antibiotic for multidrug-resistant infections, but its use is limited by the frequent onset of acute drug-induced kidney injury (DIKI). It is essential to closely monitor kidney function prior to and during colistin treatment in order to pinpoint early signs of injury and minimize long-term renal dysfunction. To facilitate this, a mouse model of colistin-induced nephrotoxicity was used to uncover novel early markers of colistin-induced DIKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…4c). The urinary secretion of KIM-1, a sensitive marker for damage in proximal tubular cells [32,33], was found to be the most sensitive of the tested biomarkers for kidney injury (Fig. 4d), followed by 2-microglobulin, clusterin, and albumin (Fig.…”
Section: Pharmacokinetics and Nephrotoxicity Of Ebl-1003 In Comparison To Gentamicinmentioning
confidence: 97%
“…4c). The urinary secretion of KIM-1, a sensitive marker for damage in proximal tubular cells [32,33], was found to be the most sensitive of the tested biomarkers for kidney injury (Fig. 4d), followed by 2-microglobulin, clusterin, and albumin (Fig.…”
Section: Pharmacokinetics and Nephrotoxicity Of Ebl-1003 In Comparison To Gentamicinmentioning
confidence: 97%
“…Thus, assuming comparable glomerular filtration rate among groups, urinary creatinine was used as a normalization element for urinary Kim-1 values. In a previous study, we showed that urinary Kim-1 outperformed urinary Cystatin-C and urinary glucose in the detection of colistin-induced kidney injury in mice 38 . Urinary Kim-1 was significantly elevated in mice treated with colistin.…”
Section: Resultsmentioning
confidence: 96%
“…Next, we assessed the effect of L-carnitine co-injection on colistin pharmacokinetics and accumulation in the kidney tissue in mice. The dose of colistin (20 mg/kg) was chosen based on our previous study, showing that all animals treated at this dose showed signs of acute kidney injury after 7 days of treatment 38 . The dose of L-carnitine (30 mg/kg) was chosen based on previous studies in rodents, and as well as on available pharmacokinetics and safety data generated in patients with primary carnitine deficiency 39 , 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, assuming comparable glomerular filtration rate among groups, urinary creatinine was used as a normalization element for urinary Kim-1 values. In a previous study, we showed that urinary Kim-1 outperformed urinary Cystatin-C and urinary glucose in the detection of colistin-induced kidney injury in mice (Samodelov et al 2019). Urinary Kim-1 was significantly elevated in mice treated with colistin.…”
Section: Colistin-induced Nephrotoxicity In Mice Co-injected With L-c...mentioning
confidence: 92%
“…Next, we assessed the effect of L-carnitine co-injection on colistin pharmacokinetics and accumulation in the kidney tissue in mice. The dose of colistin (20 mg/kg) was chosen based on our previous study, showing that all animals treated at this dose showed signs of acute kidney injury after 7 days of treatment (Samodelov et al 2019). The dose of L-carnitine (30 mg/kg) was chosen based on previous studies in rodents, and as well as on available pharmacokinetics and safety data generated in patients with primary carnitine deficiency (Jafari et al 2013;Rasmussen et al 2015).…”
Section: Effect Of L-carnitine On the Antimicrobial Activity And Phar...mentioning
confidence: 99%